Numerical and experimental studies of a multi-purpose floating TLP structure for combined wind and wave energy exploitation - MAZARAKOS, THOMAS; KONISPOLIATIS, DIMITRIOS; KATSAOUNIS, GEORGIOS; POLYZOS, STYLIANOS; MANOLAS, DIMITRIOS; VOUTSINAS, SPYROS; SOUKISSIAN, TAKVOR; MAVRAKOS, SPYRIDON A. (Mediterranean Marine Science, 2019)
This paper summarizes the coupled hydro-aero-elastic analysis of a multi-purpose floating structure suitable for offshore wind and wave energy exploitation. The analysis incorporates properly the solutions of the diffraction and the pressure- and motion- dependent radiation problems around the floating structure and the aerodynamics of a 5 MW Wind Turbine (WT). Finite water depths are considered, the structure being floating under the action of regular surface waves. The platform encompasses three hydrodynamically interacting Oscillating Water Column (OWC) devices consisting of concentric vertical cylinders, moored through tensioned tethers in a TLP concept. Details concerning the numerical and experimental modelling of the system are presented and the numerical results are compared against experimental data.